The Influence of Promotion, Halal Label, and Price on Muslim Consumer Decisions to Buy Food and Beverages in Online Applications with Discounts as A Moderating Variable in The City of Medan - Amir Fauzi Hasibuan; Nur Ahmadi Bi Rahmani; Rahmat Daim Harahap (Management Department Universitas Islam Negeri Sumatera Utara, 2023)
This study uses quantitative methodology with Promotion, Halal Label, Price variable and Consumer Decisions as dependent variable. The analysis methods used are Descriptive Analysis, Instrument Test, Classical Assumption Test, Multiple linear regression test with moderating variables using MRA, F-Test, and T-Test. The promotion significantly affects consumer decisions and affects consumer decisions (with MRA Test). The halal label has a t-count value of 10.686> 1.983, and it can be concluded that it affects consumer decisions. The results of the MRA analysis, the X2X4 result is 0.00 <0.05, and the t-count value is 13.542> 1.983. It is concluded that the halal label affects consumer decisions. Price has a sig value of 0.00 <0.05 and a tcount value of 19.255> 1.983. So, price affects consumer decisions. The results of the MRA analysis obtained that the value of X3X4 is equal to 0.00 <0.05, and the tcount value is 18.166> 1.983. It is concluded that price affects consumer decisions. Discount has a sig value of 0.00 <0.05 and a tcount value of 12.012> 1.983. It is concluded that price affects consumer decisions after the variable moderation discount can strengthen the influence of promotion variables, halal labeling, and price on consumer decisions.Keywords: Consumer decision, halal label, price, promotion